Case Study on Genesis Infectious Bursal Disease (IBD) on Broiler chickens at PT. Aretha Nusantara Farm Bandung - Miftakhul Zannah; Aan Awaludin; Dyah Laksito Rukmi; Suluh Nusantoro; Satria Budi Kusuma (Universitas Tidar, 2020)
Infectious Bursal Disease (IBD) known as Gumboro is a high frequently found virus that has an acute trait. It occurs on broiler chickens and easily transmitted among them especially during the maintenance period. The targets of this virus are the cell in the bursa of fabricius and various lymphoid organs. Therefore, the IBD virus infection causes interference to the immune system. Moreover, the observation of clinical symptoms showed that in the Arjasari 2 stall found the changes in clinical symptoms on broiler chickens. It covers weakness and lethargy, decreased appetite, hanging wings, whitish watery diarrhea, and dirty cloaca. Besides, during the maintenance period found a high mortality rate. Based on the results of a necropsy, several organs have changed in broiler chickens aged 17-33 days. Changes in the bursa of fabricius experiencing organ hemorrhage air sacs that become inflamed (airsacculitis), and hemorrhages on the heart, thus space indicating an IBD. Results from the study showed that the field methods for diagnosis with a view of the clinical symptoms, the mortality rate, and a necropsy can be used as a method for the field diagnosis of IBD. Changes in the post mortem organ can be used as reinforcement to the clinical diagnosis of IBD, especially changes or damage to the bursa of fabricius.